STRATEGI EDUKASI KESEHATAN REPRODUKSI PADA REMAJA MELALUI PENDEKATAN KOMUNIKASI PERUBAHAN PERILAKU - Dhina Widayati (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
During adolescence, several changes occur, one of which is changes in the reproductive organs and hormonal regulation which often cause problems in reproductive health. In solving adolescent reproductive health problems, proper knowledge is needed. Knowledge improvement can be done through education. One of the educational strategies that can be applied is through behavior change communication methods. The purpose of this service activity is to provide education to adolescents regarding reproductive health through a communication approach for behavior change. The method of implementing this activity is through counseling and simulation involving 30 teenagers. The implementation of service activities is carried out in 3 activities, namely: education about the development of reproductive organs, education about reproductive health, and simulations on how to maintain reproductive health. The result of service activities is an increase in the knowledge and ability of adolescents in maintaining reproductive health, from most (60%) in the sufficient category (before the activity) to almost all (90%) in the good category. Education with communication, information, and simulation approaches can increase adolescents' understanding of reproductive organs and reproductive health so that their perceptions become positive and they can maintain the health of reproductive organs. The education method with communication, information, and simulation approach can be used as a medium for delivering information on the management of reproductive health in adolescents.